The development and application of fish scale waste for tissue engineering applications : waste-to-resource conversion of resource resilient materials - Wang, Jun Kit (2017)
Collagen is the most abundant protein found in the human body and plays an important role in directing cellular behavior such as cell adhesion, proliferation and differentiation. Hence, collagen is one of the most studied biomaterial for tissue engineering (TE) applications. However, the current principle source of collagen is mainly from mammalian animals, which may contain some risk of zoonotic disease transmission and which may have restricted used for some religious and ethnic communities. Therefore, alternative sources of collagen such as fish-derived collagen, which has no risk of disease transmission to humans and is not associated with any religious barriers, is highly desirable. However, the potential applicability of fish-derived collagen is highly dependent on its thermal stability, which is affected by the living environment and the body temperature of the fish species. In general, collagen with high thermal stability is required to provide the necessary thermo-mechanical strength and degradation stability when implanted in vivo. Although studies have shown that the freshwater fish-derived collagen exhibits better thermal stability as compared to seawater fish-derived collagen, to our knowledge, limited studies have been carried out to compare the fish-derived collagen from different fish species, particular those extracted from fish scales. Moreover, fish scales also consist of hydroxyapatite (HA), which is the main component of bone with excellent osteoconductive properties to promote bone regeneration. Therefore in this thesis, fish scale-derived collagen (FSCol) and fish scale-derived HA (FSHA) were extracted from different fish species and the potential of the extracted products for various TE applications were explored. Findings from the studies demonstrated that Type I FSCol was successfully extracted using a modified acid solubilization extraction method with preserved structural quality (i.e. retention of triple helical structures) where snakehead scale-derived collagen (SHCol) exhibited significant higher (p < 0.05) thermal stability as compared to other species. Meanwhile, a monophase HA was successfully extracted using heat-sintering method. Subsequently, the extracted FSCol was conjugated onto polyvinylidene fluoride (PVDF) substrates to improve the cytocompatibility of PVDF substrates. Overall, SHCol-conjugated PVDF films demonstrated better hemocompatibility properties as compared to other fish species, and thus is a promising material to be used for blood contacting applications. The SHCol was then chemically-modified and crosslinked to produce a water-soluble collagen with improved physicochemical properties as a potential drug carrier for biomedical applications. In addition, the chemically-modified SHCol (i.e. methylated SHCol) promoted growth of blood vessels (BVs) and lymphatic vessels (LVs) during in vivo studies. From the histological results, the uncrosslinked methylated SHCol promoted greater cellular infiltration, thus making it most suitable for wound healing applications. On the other hand, the methylated SHCol crosslinked with 1,4-butanediol diglycidyl ether (BDE) crosslinker significantly promoted (p < 0.05) the formation and growth of LVs, thus making it suitable for treatment of lymphedema or other inflammatory related diseases. Lastly, a biocomposite scaffold consisting of both SHCol and snakehead scale-derived HA (SHHA) was fabricated. Based on the in vitro cellular studies, the presence of SHHA and SHCol significantly promoted (p < 0.05) the cell-material interactions of pre-osteoblast cells, and thus has potential to be used for bone TE applications. Taken together, this thesis demonstrated the potential of the extracted FSCol and FSHA as a resource resilient, cost effective source of waste-to-resource bioactive materials for various biomedical applications.